PENGARUH PEMBERIAN KIE (KOMUNIKASI INFORMASI EDUKASI) PERSIAPAN PERSALINAN DAN NIFAS TERHADAP KEJADIAN POSTPARTUM BLUES - Dwi Winarni; Krisdiana Wijayanti; Ngadiyono Ngadiyono (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2017)
Postpartum blues iceberg phenomenon which is difficult in detection because people still think of psychological disorders is a natural thing as a mater-nal instinct and protective attitude towards her baby. The incidence of postpartum blues is quite high at 26-85% and continues with postpartum depression with varying amounts of 5-25% after the mother gives birth. The purpose of this study to know is there any influence of IEC (Information Education Communication) preparation for labor on the incidence of postpartum blues. The research method with quasi experiment with post test with control group which makes it possible to compare the results of sampling diberikan.Teknik intervention by total sampling. Results showed that respondents with age healthy reproductive 33 respondents (83%), parity primiparous and multiparous same that 20 (50%), the level of elementary education (13%), middle (38%), high school / vocational (43%), D3 / S1 (8%), job: working mothers (38%), not working (62%), treatment groups: normal (80%), postpartum blues (20%), the control group: normal (45%), postpartum blues (55%). Bivariate analysis of these studies by Mann Whitney Test results obtained pvalue = 0.024 0.005, which means there is the effect of KIE childbirth and post-partum the incidence of postpartum blues From the results of this study are expected health workers, especially midwives need to provide IEC in third trimester pregnant women about childbirth and postpartum in order to reduce the incidence of postpartum blues